PERAN STUDI BANDING KE SEKOLAH PENGGERAK DALAM MENINGKATKAN KINERJA GURU DI TKQ BINAUL IMAN - Nurjanah, Siti; Nasem, Nasem; Putri Hendrayana, Saniyya (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Teachers are the implementers of the teaching and learning process in the classroom, the success of their teaching is largely determined by their performance. Good teacher performance has several indicators, including mastery of the material, selection of teaching methods, interaction with students, evaluation, self-development, discipline, classroom management and parental involvement. The purpose of this research is an effort to improve teacher performance at TKQ Binaul Iman. This is deemed very necessary because teacher performance at the institution is not optimal. A comparative study activity to the driving school is one of the activities attempted by the school to increase motivation and abilities so that teacher performance can be improved. The research method chosen is qualitative by describing the results of research findings at the two driving schools that are the targets of the comparative study. The comparative study activity provides a place for direct observation by seeing good practices in classroom learning, becoming a means to discuss obstacles in classroom learning. With the comparative study activity to the driving school is felt to increase the motivation of TKQ Binaul Iman teachers in improving teaching skills in the classroom, can absorb good practices that can be adopted and then applied to the institution so that development achievements can be achieved, student abilities increase, and public trust begins to grow. In efforts to improve teacher performance, there are several factors that influence performance, namely motivation and commitment, ability and competence, work environment, and support from schools and the government.